2019
DOI: 10.14309/01.ajg.0000600704.10755.67
|View full text |Cite
|
Sign up to set email alerts
|

2793 Primary Biliary Cholangitis (PBC): Any Differences Between Males and Females?

Abstract: INTRODUCTION: PBC (primary biliary cholangitis) is a cholestatic autoimmune liver disease characterized by destruction of small intrahepatic bile ducts. PBC predominantly affects females but has also been reported in males. Characteristics of PBC in males have not been well described. We aimed to determine the incidence, characteristics, and prognosis of male patients with PBC as compared to females. METHODS: We performed a retrospective chart review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Women are undoubtedly more susceptible to autoimmunity than men and are more likely to suffer from symptoms of pruritus and skin pigmentation in PBC, with pruritus occurring more frequently while taking oral contraceptives and during.pregnancy [ 13 , 14 ]. Clinical studies have also found that PBC patients are more likely to undergo hysterectomy for menstrual irregularities and that PBC patients are more likely to receive hormone replacement therapy [ 15 , 16 ].…”
Section: Sex Hormones and Endocrinologymentioning
confidence: 99%
“…Women are undoubtedly more susceptible to autoimmunity than men and are more likely to suffer from symptoms of pruritus and skin pigmentation in PBC, with pruritus occurring more frequently while taking oral contraceptives and during.pregnancy [ 13 , 14 ]. Clinical studies have also found that PBC patients are more likely to undergo hysterectomy for menstrual irregularities and that PBC patients are more likely to receive hormone replacement therapy [ 15 , 16 ].…”
Section: Sex Hormones and Endocrinologymentioning
confidence: 99%
“…In terms of diagnostics, anti-mitochondrial antibody is absent in 15% of women with PBC while anti-mitochondrial antibody negativity typically excludes a diagnosis of PBC in men. 88 Women are typically younger and more symptomatic than men at diagnosis. Women report more fatigue and pruritis, which may relate to hormonal differences.…”
Section: Fibrotic Diseasesmentioning
confidence: 99%